The study of facilities in UiTM Shah Alam campus as research university / Marlia Hani Shahril - Shahril, Marlia Hani (2012)
UiTM is one university in Malaysia who want recognized and given the title as part of a Research University in Malaysia. Among the factors to be considered by the UiTM in the process of obtaining recognition as a research university is to strengthen the physical needs. Consistent with efforts to improve the quality and level of research at the Universiti Technologi Mara (UiTM), university physical improvement must be improved. The physical requirements required by the postgraduate students and doctors of philosophy are in terms of improving the quality of library services and resources in teaching and learning facilities. Both of the physical needs are important and should be taken into account to achieve the level of Research Universities. To achieve the status Research University, UiTM need to comply with and fulfill the needs and conditions stipulated by the Ministry of Higher Education, and the facilities that need to be considered is in terms of classroom and library facilities. Both facilities are important in helping students, particularly post-graduate students and doctoral of philosophy in producing the quality research.